Synergistic Interactions Between Warming and Elevated Atmospheric CO 2 Increase Soil Organic Carbon Sequestration - Ruiqi Yao; Yike Zhang; Wolfgang Wanek; Zhongkui Luo; Haoran Fu; Scott X. Chang; Cesar Terrer; Mingkai Jiang; Tida Ge; Guopeng Liang; Yuanhe Yang; Yiqi Luo; et al. (Global Change Biology, 2026)
Warming and elevated CO 2 (eCO 2 ) are two potentially opposing climate‐carbon (C) feedback mechanisms that modulate the magnitude of the land C sink, with warming decreasing and eCO 2 increasing C sequestration. However, their net effect on soil organic C (SOC)—the largest terrestrial C stock—remains uncertain. Here, we quantify how warming, eCO 2 , and their interactions influence SOC by using 5558 paired observations from 1392 global studies across ecosystem types. Our study shows that warming reduces SOC by 8.0%, primarily by suppressing aboveground C inputs (−1.0%) and decreasing microbial C use efficiency (−9.9%). Concurrent warming and eCO 2 increase SOC by 7.6%—a synergistic effect larger than eCO 2 alone (+4.8%), primarily contributed by croplands. This outcome may result from increases in plant C inputs and soil nitrogen availability under eCO 2 , which facilitate microbial C assimilation and necromass formation (+3.9%). These processes promote the accumulation of mineral‐associated C (+9.9%) and offset the negative effects of warming. The combined effect of warming and eCO 2 is projected to increase SOC by 27.4 Pg C by 2100. Our findings highlight that synergistic interaction between warming and eCO 2 increases SOC sequestration and enhances SOC stability under future climate change.

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Combining paleocurrents and sea level in a least-cost pathway model of human dispersal from Sunda to Sahul, 65–45,000 years ago - Marisa Borreggine; Evelyn M. Powell; Minmin Fu; Xiaoting Yang; Elle Weeks; Boer Zhang; Kendra Wilkinson; Jerry X. Mitrovica; Christian Tryon; Richard Meadow (Quaternary Science Reviews, 2026)

The proteomic blueprint of human aging: a 50-year, 13-tissue atlas - Matthew X. Fang; Tian-Min Fu (Science China Life Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Assessing the response of terrestrial water storage to climate warming in China by coupling CMIP6 multi-model ensembles, hydrological model, and machine learning algorithms - Xiaoyan Cao; Jiali Ju; Chuanhao Wu; Pat J.-F. Yeh; Min Shi; Ashraf Dewan; Yongze Song; Xueyuan Zhang; Tian Yao; Yufei Jiao; Qiongfang Li; Shanshui Yuan; et al. (Climatic Change, 2026)

Hepatocyte proteome destabilization and novel targets for PFASs unveiled through combined thermal proteome profiling and deep transfer learning - Zimeng Wu; Yue Zou; Kang Yang; Xiaomei Yu; Zhiqiang Fu; X. Chris Le; Jingwen Chen (Journal of Hazardous Materials, 2025)

Revealing distribution patterns of river obstructions in China via deep-learning and satellite imagery - Mingxia He; Jie Niu; Dongdong Liu; Yong Fu; Qixin Wu; Shaoqi Zhou; Pan Wu; Chuanhao Wu; Bill X. Hu (Journal of Hydrology, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

Improving groundwater vulnerability assessment using machine learning - Juanjuan Fu; X. Chris Le (Journal of Environmental Sciences, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Performance and mechanism of NiO/La-KTaO3 composite photocatalysts for UV degradation of isoamyl xanthate in synthetic flotation wastewater - X. Xu; L. Zhu; C. Chen; C. Luo; Z. Jin; Z. Sun; Z.T Fu (International Journal of Environmental Science and Technology, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Ammonia inhibition in anaerobic digestion of organic waste: a review - J. Yang; J. Zhang; X. Du; T. Gao; Z. Cheng; W. Fu; S. Wang (International Journal of Environmental Science and Technology, 2025)
Anaerobic digestion (AD) has become the technology of choice for organic waste treatment as an environmentally beneficial and sustainable waste treatment technology. However, the nitrogen content of these organic waste streams is generally high. Ammonia is produced in the biodegradation of nitrogenous organic matter. Low concentrations of ammonia favour AD, but high concentrations can lead to digestive system failure. To address the issue of ammonia inhibition and ensure the stability of the digestive system, numerous physical, chemical, and biologicalmethods aimed at controlling ammonia levels and/or strengthening the biological processes have been proposedand developed. Literature evidence suggests that differences in AD reaction conditions and microbial sources result in different tolerances of the digestive system to ammonia and nitrogen. This paper summarises and compares the inhibitory effects of ammonia nitrogen under different conditions and the existing regulatory measures to alleviate ammonia nitrogen inhibition. In addition, since the core of the digestive system is microorganisms, this paper explains the mechanism of ammonia stress especially at the microbial level, and in this way, it explores the future direction of research using biofortification. This review provides a theoretical reference for solving the problem of ammonia nitrogen inhibition.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

R&D investment and corporate total factor productivity under the heterogeneous environmental regulations: evidence from Chinese micro firms - X. Ding; Y. Zhang; Y. Fu; Z. Xu (International Journal of Environmental Science and Technology, 2025)

Optimizing tradeoff strategies of soil microbial community between metabolic efficiency and resource acquisition along a natural regeneration chronosequence - Qiang Lu; Zhengfeng An; Beibei Zhang; Xiaoqiang Lu; Xia Mao; Jiaqi Li; Scott X. Chang; Yan Liu; Xiangxiang Fu (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Distinct effects of canopy vs understory and organic vs inorganic N deposition on root resource acquisition strategies of subtropical Moso bamboo plants - Lin Wang; Baogang Zhang; Yunying Fang; Huajun Yin; Shenglei Fu; Scott X. Chang; Yanjiang Cai (Science of The Total Environment, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

An indeterministic fractional two-stage inter-regional energy system optimization model: A case study for the Province of Shanxi, China - Y.L. Zheng; G.H. Huang; Y.P. Li; J.P. Chen; X. Zhou; B. Luo; Y.P. Fu; L.J. Lin; Z.P. Xu; W.C. Tang (Journal of Cleaner Production, 2024)

N-carbamylglutamate, a promising functional feed additive in swine production: A review - Y.X. Li; V.R. Moreira; L.S. Wang; Q.L. Liu; P.D. Gao; X.J. Zhang; X. Fu (Animal Feed Science and Technology, 2023)

Effects of ball milling on biochar adsorption of contaminants in water: A meta-analysis - Jean Damascene Harindintwali; Chao He; Leilei Xiang; Qingyuan Dou; Yu Liu; Mingyi Wang; Xin Wen; Yuhao Fu; Mahbub Ul Islam; Scott X. Chang; Stephan Kueppers; Sabry M. Shaheen; et al. (Science of The Total Environment, 2023)

Causal relations between the loop current penetration and the inflow/outflow conditions inferred with a rigorous quantitative causality analysis - Yang Yang; Guanqi Fu; X. San Liang; Robert H. Weisberg; Yonggang Liu (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Preparation of carbonaceous adsorption composite with refinery sludge for butyl xanthate and diethyldithiocarbamate removal in flotation wastewater - P. Fu; H. Yang; Q. Zhang; X. Li (International Journal of Environmental Science and Technology, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

Cre-mediated autoexcision of selectable marker genes in soybean, cotton, canola and maize transgenic plants - Xudong Ye; Zarir Vaghchhipawala; Edward J. Williams; Changlin Fu; Jinyuan Liu; Fengming Lu; Erin L. Hall; Shirley X. Guo; LaRee Frank; Larry A. Gilbertson (Plant Cell Reports, 2023)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

The Ocean's labile DOC supply chain - Mary Ann Moran; Frank X. Ferrer‐González; He Fu; Brent Nowinski; Malin Olofsson; McKenzie A. Powers; Jeremy E. Schreier; William F. Schroer; Christa B. Smith; Mario Uchimiya (Limnology and Oceanography, 2022)
Microbes of the surface ocean release, consume, and exchange labile metabolites at time scales of minutes to days. The details of this important step in the global carbon cycle remain poorly resolved, largely due to the methodological challenges of studying a diverse pool of metabolites that are produced and consumed nearly simultaneously. In this perspective, a new compilation of published data builds on previous studies to obtain an updated estimate of the fraction of marine net primary production that passes through the labile dissolved organic carbon (DOC) pool. In agreement with previous studies, our data mining and modeling approaches hypothesize that about half of ocean net primary production is processed through the labile DOC pool. The fractional contributions from three major sources are estimated at 0.4 for living phytoplankton, 0.4 for dead and dying phytoplankton, and 0.2 for heterotrophic microbes and mesoplankton.

Failure modes of slope stabilized by frame beam with prestressed anchors - J. J. Zhang; J. Y. Niu; X. Fu; L. C. Cao; S. J. Yan (European Journal of Environmental and Civil Engineering, 2022)

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Investigation of permanent displacements of near-fault seismic slopes by a general sliding block model - Yingbin Zhang; Chenlin Xiang; Pengcheng Yu; Lianheng Zhao; John X. Zhao; Haiying Fu (Landslides, 2022)

Back-analysis of Donghekou landslide using improved DDA considering joint roughness degradation - Jinmei Wang; Yingbin Zhang; Yanlong Chen; Qingdong Wang; Chenlin Xiang; Haiying Fu; Pan Wang; John X. Zhao; Lian-heng Zhao (Landslides, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Characteristics changes in banana peel coagulant during storage process - Y. Fu; X. J. Meng; N. N. Lu; H. L. Jian; Y. Di (International Journal of Environmental Science and Technology, 2019)

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Sequence subdivision and development characteristics of low-accommodation non-marine basins: a case study of the Yanchang Formation in the Ordos Basin - S. Fu; Z. Liu; Y.-Z. Li; Y.-R. Guo; X.-M. Xu; J.-J. Liu; X. D. Hu (Australian Journal of Earth Sciences, 2018)

Quantitative discrimination of normal fault segment growth and its geological significance: example from the Tanan Depression, Tamtsag Basin, Mongolia - H. X. Wang; X. F. Fu; S. R. Liu; R. Chu; B. Liu; P. P. Shi (Australian Journal of Earth Sciences, 2018)

Analysis of the Spatial Variation and Identification of Factors Affecting the Water Resources Carrying Capacity Based on the Cloud Model - K. Cheng; Q. Fu; J. Meng; T. X. Li; W. Pei (Water Resources Management, 2018)

Evaluation of bioactivity of phenolic compounds from the brown seaweed of Sargassum fusiforme and development of their stable emulsion - N. Liu; X. Fu; D. Duan; J. Xu; X. Gao; L. Zhao (Journal of Applied Phycology, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

CXCL10 suppression of hem- and lymph-angiogenesis in inflamed corneas through MMP13 - Nan Gao; Xiaowei Liu; Jiayin Wu; Juan Li; Chen Dong; Xinyi Wu; Xiao Xiao; Fu-Shin X. Yu (Angiogenesis, 2017)

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

Abrp, a new gene, confers reduced susceptibility to tetracycline, glycylcine, chloramphenicol and fosfomycin classes in Acinetobacter baumannii - X. Li; J. Quan; Y. Yang; J. Ji; L. Liu; Y. Fu; X. Hua; Y. Chen; B. Pi; Y. Jiang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Isolation and identification of a new reovirus associated with mortalities in farmed oriental river prawn, M acrobrachium nipponense (de Haan, 1849), in C hina - S Zhang; X Shu; L Zhou; B Fu (Journal of Fish Diseases, 2016)

Catalytic behavior and synergistic effect of nonthermal plasma and CuO/AC catalyst for benzene destruction - C. He; L. Cao; X. Liu; W. Fu; J. Zhao (International Journal of Environmental Science and Technology, 2015)

Efficiency and Accuracy Verification of the Explicit Numerical Manifold Method for Dynamic Problems - X. L. Qu; Y. Wang; G. Y. Fu; G. W. Ma (Rock Mechanics and Rock Engineering, 2015)

Identification of the trehalose-6-phosphate synthase gene family in winter wheat and expression analysis under conditions of freezing stress - D. W. XIE; X. N. WANG; L. S. FU; J. SUN; W. ZHENG; Z. F. LI (Journal of Genetics, 2015)

The role of heat shock proteins in oxidative stress damage induced by Se deficiency in chicken livers - C. P. Liu; J. Fu; F. P. Xu; X. S. Wang; S. Li (BioMetals, 2015)

Effects of fasting and feeding on the fast‐start swimming performance of southern catfish Silurus meridionalis - G. J. Yan; X. K. He; Z. D. Cao; S. J. Fu (Journal of Fish Biology, 2015)
This study investigated the effects of fasting and feeding on the fast‐start escape swimming performance of juvenile southern catfish Silurus meridionalis , a sit‐and‐wait forager that encounters extreme fasting and famine frequently during its lifespan. Ten to 30 days of fasting resulted in no significant change in most of the variables measured in the fast‐start response except a 20–30% decrease in the escape distance during the first 120 ms ( D 120ms ) relative to the control group (48 h after feeding). The ratio of the single‐bend ( SB ) response (lower energetic expenditure) to the double‐bend ( DB ) response increased significantly from 0% in the control group to 75 and 82·5% in the 20 and 30 day fasting groups, respectively. Satiated feeding (25% of body mass) resulted in a significantly lower (36·6%) maximum linear velocity ( V max ) and a significantly lower (43·3%) D 120ms than in non‐fed fish (control group, 48 h after feeding). Half‐satiated feeding (12·5% of body mass), however, showed no significant effects on any of the measured variables of the fast‐start response relative to control fish. It is suggested that the increase in the ratio of SB : DB responses with fasting in S. meridionalis may reflect a trade‐off between energy conservation and maintaining high V max , while variables of fast‐start performance were more sensitive to feeding than fasting might be an adaptive strategy to their foraging mode and food availability in their habitat.

Canonical transient receptor potential 4 and its small molecule modulators - Jie Fu; ZhaoBing Gao; Bing Shen; Michael X. Zhu (Science China Life Sciences, 2015)

A novel fish cell line derived from the brain of Chinese perch Siniperca chuatsi : development and characterization - X. Fu; N. Li; Y. Lai; X. Luo; Y. Wang; C. Shi; Z. Huang; S. Wu; J. Su (Journal of Fish Biology, 2015)
In this study, a continuous cell line (named as CPB ) was established from Siniperca chuatsi brain and has been subcultured >140 times. CPB cell line predominantly consisted of fibroblast‐like cells that could grow better in Leibovitz's L‐15 supplemented with 10% foetal bovine serum at 28° C. Polymerase chain reaction amplification of 18s recombinant (r)RNA confirmed the origin of this cell line from S. chuatsi . The CPB cell line was cryopreserved at different passage levels and revived successfully with 80–90% survival. The cell line was further characterized by chromosome number and transfection. The CPB cells were highly susceptible to infectious spleen and kidney necrosis virus ( ISKNV ) with a titre of 6·58–6·62 log TCID 50 ml −1 and numerous ISKNV particles were observed in the cytoplasm by transmission electron microscopy. At the same time, ISKNV infection was confirmed by reverse transcriptase polymerase chain reaction, immunodot blot and individual challenge experiments. The development and characterization of a new brain cell line from S. chuatsi were described in this study and it could be used as an in vitro tool for propagation of ISKNV and gene expression studies.

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

Field Evaluation of Different Wavelengths Light-Emitting Diodes as Attractants for Adult Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - L X Zheng; Y Zheng; W J Wu; Y G Fu (Neotropical Entomology, 2014)

Oncogenic and tumor suppressive roles of microRNAs in apoptosis and autophagy - Y. Chen; L. L. Fu; X. Wen; B. Liu; J. Huang; J. H. Wang; Y. Q. Wei (Apoptosis, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

A new flavanocoumarin from the root of Flemingia philippinensis - Manqin Fu; Dun Deng; Riming Huang; Nenling Zhang; Zhiwei Su; Samuel X. Qiu (Natural Product Research, 2013)

Numerical description of coalbed methane desorption stages based on isothermal adsorption experiment - Zheng Zhang; Yong Qin; Geoff X. Wang; XueHai Fu (Science China Earth Sciences, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

A New Vector for Identification of Prokaryotes and Their Variable-Size Genomes - Tao Hou; Fu Liu; Caixia X. Lin; Dingyuan Y. Li (Current Microbiology, 2013)

Microbiologic characteristics of pathogenic bacteria from hospitalized trauma patients who survived Wenchuan earthquake - B. Zhang; Z. Liu; Z. Lin; X. Zhang; W. Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Correlation between plasma amino acid profiles and the various stages of hepatitis B infection - J. Yang; J. He; H. Cao; X. Zhao; S. Fu; H. Lu; Y. Chen; X. Pan; L. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

How are seasonal prediction skills related to models’ performance on mean state and annual cycle? - June-Yi Lee; Bin Wang; I.-S. Kang; J. Shukla; A. Kumar; J.-S. Kug; J. K. E. Schemm; J.-J. Luo; T. Yamagata; X. Fu; O. Alves; B. Stern; et al. (Climate Dynamics, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

Vertical Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Soil Cores Taken from a Typical Electronic Waste Polluted Area in South China - Z. Z. Yang; Y. F. Li; Y. X. Hou; H. Y. Liang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Impacts of cascade run-of-river dams on benthic diatoms in the Xiangxi River, China - N. Wu; T. Tang; X. Fu; W. Jiang; F. Li; S. Zhou; Q. Cai; N. Fohrer (Aquatic Sciences, 2010)

Co-location of seed oil content, seed hull content and seed coat color QTL in three different environments in Brassica napus L. - X. Y. Yan; J. N. Li; F. Y. Fu; M. Y. Jin; L. Chen; L. Z. Liu (Euphytica, 2009)

Polybrominated Diphenyl Ethers in the Soil of Typical Industrial City - K. Li; S. Fu; Z. Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Influence of dent corn genetic backgrounds on QTL detection for plant-height traits and their relationships in high-oil maize - M. Wei; J. Fu; X. Li; Y. Wang; Y. Li (Journal of Applied Genetics, 2009)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Composition, Distribution, and Characterization of Polybrominated Diphenyl Ethers in Sandstorm Depositions in Beijing, China - S. Fu; Z. Z. Yang; L. Zhang; K. Li; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Phylogeographical analysis of an estuarine fish, Salanx ariakensis (Osmeridae: Salanginae) in the north‐western Pacific - X. Hua; W. Wang; W. Yin; Q. He; B. Jin; J. Li; J. Chen; C. Fu (Journal of Fish Biology, 2009)
This study extended the geographic coverage of a previous study to explore population genetic structure and demographic history in the Ariake icefish Salanx ariakensis from three populations of continental coastlines and one island population in the north‐western Pacific based on a partial sequence of the mitochondrial cytochrome b gene. The S. ariakensis showed high genetic diversity and strong genetic structure. Phylogenetic analysis showed a shallow gene tree with no clear phylogeographical structure. Contiguous range expansion and restricted gene flow were inferred to be main population events by nested‐clade analysis. Significant genetic differentiations between populations could be attributable to negligible gene flow by coalescent analysis. High nucleotide diversity of each population was due to geographic mixing of heterogenous haplotypes during lowering sea levels of the Pleistocene. These findings indicate that cycles of geographic isolation and secondary contact happened in the Pleistocene glacial–interglacial cycles shaping genetic structure and population demography of S. ariakensis .

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Polybrominated Diphenyl Ethers in Mudsnails (Cipangopaludina cahayensis) and Sediments from an Electronic Waste Recycling Region in South China - Z. Z. Yang; X. R. Zhao; Z. F. Qin; S. Fu; X. H. Li; X. F. Qin; X. B. Xu; Z. X. Jin (Bulletin of Environmental Contamination and Toxicology, 2009)

Composition, Distribution, and Characterization of Polycyclic Aromatic Hydrocarbons in Soil in Linfen, China - S. Fu; H. X. Cheng; Y. H. Liu; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Polycyclic Aromatic Hydrocarbons Residues in Sandstorm Depositions in Beijing, China - S. Fu; K. Li; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Composition, Distribution and Characterization of Polybrominated Diphenyl Ethers (PBDEs) in the Soil in Taiyuan, China - K. Li; S. Fu; Z. Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Polycyclic Aromatic Hydrocarbons Residues in Sandstorm Depositions in Beijing, China - S. Fu; K. Li; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Organochlorine Pesticides in the Soil in Linfen, China - H. X. Cheng; S. Fu; Y. H. Liu; D. S. Li; J. H. Zhou; X. J. Xia (Bulletin of Environmental Contamination and Toxicology, 2008)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Composition, Distribution, and Characterization of Organochlorine Pesticides in Sandstorm Depositions in Beijing, China - S. Fu; K. Li; Z. Z. Yang; X. B. Xu (Water, Air, & Soil Pollution, 2008)

Contamination Status of Hexachlorobenzene (HCB) in Sandstorm Depositions from Beijing and the Origination Region - S. Fu; K. Li; Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Is peak postprandial oxygen consumption positively related to growth rate and resting oxygen consumption in a sedentary catfish Silurus meridionalis ? - S. J. Fu; Z. D. Cao; J. L. Peng; Y. X. Wang (Journal of Fish Biology, 2008)
The resting oxygen consumption , postprandial and post‐exercise peak oxygen consumption of 137 juvenile southern catfish Silurus meridionalis , weighing 18·5 ± 0·8 g (mean ± s . d .), were measured at 25° C to determine whether is positively related to postprandial and post‐exercise in sedentary S. meridionalis . In addition, postprandial metabolic response [ i.e. the specific dynamic action (SDA)] after a satiating meal and the growth performance as a consequence of a 3 week feeding‐growth trail were measured in 40 S. meridionalis , weighing 14·3 ± 0·2 g, at 25° C to determine whether postprandial is positively related to growth rate. Postprandial was positively correlated with , while post‐exercise was not. Both postprandial and post‐exercise were positively correlated with factorial and absolute scope. There was no significant correlation between the growth rate and postprandial in S. meridionalis . It suggested that as a sit‐and‐wait forager with low , low post‐exercise and high postprandial , the expenditure of energy for maintenance in S. meridionalis may be more closely related to digestive processes than locomotor activities.

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

CO 2 control of Trichodesmium N 2 fixation, photosynthesis, growth rates, and elemental ratios: Implications for past, present, and future ocean biogeochemistry - D. A. Hutchins; F.-X. Fu; Y. Zhang; M. E. Warner; Y. Feng; K. Portune; P. W. Bernhardt; M. R. Mulholland (Limnology and Oceanography, 2007)
Diazotrophic marine cyanobacteria in the genus Trichodesmium contribute a large fraction of the new nitrogen entering the oligotrophic oceans, but little is known about how they respond to shifts in global change variables such as carbon dioxide (CO 2 ) and temperature. We compared Trichodesmium dinitrogen (N 2 ) and CO 2 fixation rates during steady‐state growth under past, current, and future CO 2 scenarios, and at two relevant temperatures. At projected CO 2 levels of year 2100 (76 Pa, 750 ppm), N 2 fixation rates of Pacific and Atlantic isolates increased 35–100%, and CO 2 fixation rates increased 15‐128% relative to present day CO 2 conditions (39 Pa, 380 ppm). CO 2 ‐mediated rate increases were of similar relative magnitude in both phosphorus (P)‐replete and P‐limited cultures, suggesting that this effect may be independent of resource limitation. Neither isolate could grow at 15 Pa (150 ppm) CO 2 , but N 2 and CO 2 fixation rates, growth rates, and nitrogen : phosophorus (N : P) ratios all increased significantly between 39 Pa and 152 Pa (1500 ppm). In contrast, these parameters were affected only minimally or not at all by a 4°C temperature change. Photosynthesis versus irradiance parameters, however, responded to both CO 2 and temperature but in different ways for each isolate. These results suggest that by the end of this century, elevated CO 2 could substantially increase global Trichodesmium N 2 and CO 2 fixation, fundamentally altering the current marine N and C cycles and potentially driving some oceanic regimes towards P limitation. CO 2 limitation of Trichodesmium diazotrophy during past glacial periods could also have contributed to setting minimum atmospheric CO 2 levels through downregulation of the biological pump. The relationship between marine N 2 fixation and atmospheric CO 2 concentration appears to be more complex than previously realized and needs to be considered in the context of the rapidly changing oligotrophic oceans.

Composition and antimicrobial activity of the essential oil of Actinidia macrosperma from China - Y. Lu†; Y. P. Zhao†; Z. C. Wang; S. Y. Chen; C. X. Fu* (Natural Product Research, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Phthalate Ester Pollution in Urban Soil of Beijing, People's Republic of China - X. H. Li; L. L. Ma; X. F. Liu; S. Fu; H. X. Cheng; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Complete nucleotide sequences and genome characterization of double-stranded RNA 1 and RNA 2 in the Raphanus sativus-root cv. Yipinghong - L. Chen; J. S. Chen; L. Liu; X. Yu; S. Yu; T. Z. Fu; W. H. Liu (Archives of Virology, 2006)

The systematic value of pollen morphology in Smilacaceae - S.-C. Chen; X.-P. Zhang; S.-F. Ni; C.-X. Fu; K. M. Cameron (Plant Systematics and Evolution, 2006)

Effect of feeding level and feeding frequency on specific dynamic action in Silurus meridionalis - S. J. Fu; X. J. Xie; Z. D. Cao (Journal of Fish Biology, 2005)
The effect of feeding level ( F L ; 0·5 to 4% dry diet mass per wet fish body mass) and feeding frequency (once every 4 days to twice per day) on postprandial metabolic response was investigated in southern catfish Silurus meridionalis at 27·5° C. The results showed that there was no significant difference in the specific dynamic action (SDA) coefficient among the groups of different feeding levels ( P > 0·05). The duration increased from 26·0 to 40·0 h and the peak metabolic rate increased from 207·8 to 378·8 mg O 2 kg −1 h −1 when the feeding level was increased from 0·5 to 4%. The relationship between the peak metabolic rate ( R P , mg O 2 kg −1 h −1 ) and F L could be described as: R P = 175·4 + 47·3 F L ( r 2 = 0·943, n = 40, P D , h) and F L could be described as D =30·97 F L 0·248 ( r 2 =0·729, n =40, P

Effect of fasting on resting metabolic rate and postprandial metabolic response in Silurus meridionalis - S. J. Fu; X. J. Xie; Z. D. Cao (Journal of Fish Biology, 2005)
Resting metabolic rate in southern catfish of 2 and 5 day fasting groups were significantly higher than that of the 15 day fasting group ( P P P P

Intersubgenomic heterosis in seed yield potential observed in a new type of Brassica napus introgressed with partial Brassica rapa genome - W. Qian; X. Chen; D. Fu; J. Zou; J. Meng (Theoretical and Applied Genetics, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

GISH, AFLP and PCR-RFLP analysis of an intergeneric somatic hybrid combining Goutou sour orange and Poncirus trifoliata - C. H. Fu; C. L. Chen; W. W. Guo; X. X. Deng (Plant Cell Reports, 2004)

Regeneration of citrus sinensis (+) clausena lansium intergeneric triploid and tetraploid somatic hybrids and their identification by molecular markers - C. H. Fu; W. W. Guo; J. H. Liu; X. X. Deng (In Vitro Cellular & Developmental Biology - Plant, 2003)

Present-day crustal deformation in China relative to ITRF97 kinematic plate model - Y. Fu; W. Zhu; X. Wang; W. Duan; X. Wu; W. Jiao (Journal of Geodesy, 2002)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

Organochlorine Pesticide Residue in Soils from Tibet, China - S. Fu; S. Chu; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2001)

Transgenic rice as a system to study the stability of transgene expression: multiple heterologous transgenes show similar behaviour in diverse genetic backgrounds - D. Gahakwa; S. B. Maqbool; X. Fu; D. Sudhakar; P. Christou; A. Kohli (Theoretical and Applied Genetics, 2000)

Relative Lymphocytosis-Disorder Caused by Occupational Exposure to Vinyl Chloride Monomer - A. Fu ) i '; Z. x pacir; D. Barkovi '; A. Jazbec; A. Miji '; B. Labar (Bulletin of Environmental Contamination and Toxicology, 1998)

Receptive field properties of visual neurons in the avian nucleus lentiformis mesencephali - Y.-X. Fu; Hong-Feng Gao; M.-W. Guo; S.-R. Wang (Experimental Brain Research, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)